Gilles Deleuze - Molinar Min, Carlo (Philosophy Kitchen - Rivista di filosofia contemporanea, 2024)
The influence that Deleuze’s thought has exerted in the most diverse fields of knowledge is impressive, to say the least. The presence of this author is rampant and quotations from his books often become tickets to the coolest intellectual circles. In the circle of so-called theory fiction, for example, A Thousand Plateaus has risen to the status of a sacred text, as much plundered on a conceptual level as it is apeed on a stylistic level. Even in academia and the less suspicious everyday life, the ghost of Deleuze reappears with a certain obsessiveness. Theoretical philosophy courses that do not mention Deleuze’s Spinoza when discussing the notion of immanence are very rare; at the other extreme, in the agrarian sphere, in the act of weeding a field of asparagus, someone mentions the term rhizome, et voilà the vain university student returned to the earth does not hesitate to evoke Deleuzian ontology.